THE EFFECT OF BRAND IMAGE, PRODUCT QUALITY, AND PRICE ON CONSUMER LOYALTY OF PEPSODENT TOOTHPASTE PRODUCT (Case Study in the District of Turi, Sleman regency) - Widyaningrum, Dita; Kahu Lantum, MS, Drs. Alex (Accounting, 2009)
The purpose of this study are: 1) to investigate the influence brand image against consumer loyalty, 2) to assess the influence of product quality to customer loyalty, 3) to determine the effect of price to consumer loyalty, 4) to determine which variables among the three variables most influence on customer loyalty. Brands studied are brand Pepsodent toothpaste, which the respondents were taken from the users of Pepsodent toothpaste in Sub Turi, Sleman regency, Yogyakarta. This research was conducted by survey method where data is obtained by distributing questionnaires to 100 respondents. Method of sampling using non-probability sampling. Methods of data collection in this research is the questionnaire method by using the Likert Scale. While the methods of data analysis using multiple linear regression analysis, t test and F test with the help of SPSS software. The results showed that there was a positive influence between variable brand image to consumer loyalty Pepsodent toothpaste products, that there is a positive influence between the variables of product quality to customer loyalty Pepsodent toothpaste products, that there is a positive influence between the variables of price to consumer loyalty Pepsodent toothpaste products, and that the variables that most influence on consumer loyalty is a variable Pepsodent toothpaste brand image. Keywords: brand image, customer loyalty, toothpaste.